2015
DOI: 10.1039/c5cc06980g
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic C–H bond functionalisation chemistry: the case for quasi-heterogeneous catalysis

Abstract: This feature article examines the potential of heterogeneous Pd species to mediate catalytic C-H bond functionalisation processes employing suitable substrates (e.g. aromatic/heteroaromatic compounds). A focus is placed on the reactivity of supported and non-supported Pd nanoparticle (PdNPs) catalysts, in addition to the re-appropriation of well-established heterogeneous Pd catalysts such as Pd/C. Where possible, reasonable comparisons are made between PdNPs and traditional 'homogeneous' Pd precatalyst sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(71 citation statements)
references
References 118 publications
(253 reference statements)
0
71
0
Order By: Relevance
“…Recent studies of catalytic reactions have surprisingly shown that catalytically active metal complexes do not remain unchanged during the synthetic transformation [14,15]. Indeed, several transformations involving metal complexes do take place simultaneously with the catalytic reaction ( Figure 4) [14].…”
Section: Evolution Of Catalytic Systems During the Reactionmentioning
confidence: 99%
“…Recent studies of catalytic reactions have surprisingly shown that catalytically active metal complexes do not remain unchanged during the synthetic transformation [14,15]. Indeed, several transformations involving metal complexes do take place simultaneously with the catalytic reaction ( Figure 4) [14].…”
Section: Evolution Of Catalytic Systems During the Reactionmentioning
confidence: 99%
“…Among the different approaches for the definition of catalytic methodologies, the use of insoluble catalysts that operate in a heterogeneous fashion is highly intriguing and also challenging [48][49][50][51][52][53]. Significant advantages may derive from the adoption of this strategy with the reduction of waste produced, provided that an easy recovery and reuse of the catalyst is achieved.…”
Section: Heterogeneous Catalysis In Greener Mediamentioning
confidence: 99%
“…Hg(0) is known to form amalgams with a variety of metals in their zero oxidation state (Reay and Fairlamb, 2015). Hence, if Pd dissociates from the solid Pd 0.02 Ce 0.98 O 2-, it would bind with Hg(0) thereby quenching its catalytic activity.…”
mentioning
confidence: 99%
“…However, the leaching of palladium from the catalyst is still the main problem, even though most researchers have reported that their catalysts can be recycled by the redeposition of Pd onto the support (Redon, Peña and Crescencio, 2014). This is due to the quasi-heterogeneous mechanism of the Sonogashira cross-coupling reaction via the solvated palladium clusters (Reay and Fairlamb, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation